AN AUDIT OF WHETHER PRESCRIBED DOSES ARE MEASURABLE ON THE GRADUATIONS OF ONE ORAL SYRINGE. Issue 9 (17th August 2016) - Balsara, Jigna; Fletcher, Penny
Abstract : Aim: In paediatrics drugs are prescribed as mg/kg doses to facilitate accurate dosing. Anecdotally, some drugs are prescribed in such a way that the volume to be given is difficult to measure which may lead to inaccuracies and potential for error. Locally, errors have been reported where there has been a misunderstanding of the required dose, especially when decimal points are involved. This audit aimed to evaluate doses prescribed for in-patient children and evaluate whether they can be measured using the printed markings of one oral syringe. Method: Data were collected for paediatric in-patients between 16th February and 27th March 2015 from paper drug charts and an electronic prescribing system depending which was in use in each area. Specific data on patient age, weight and prescribed dose were collected. Volumes were then calculated using the enteral products kept in the Trust formulary, including unlicensed specials. The prescribed volumes were reviewed against the Medicina Home® enteral syringes to see if they were measurable on the printed graduations of one oral syringe (in line with local dispensing standards). If they could not be measured, the percentage dose rounding required was calculated to see if doses could be rounded. A judgement was then made as to whether this was within an acceptable safe dose limit. Results: Data for 560 individual medication orders for oral medicine were collected, 257 from electronic prescribing and 303 from paper charts. Of these 457 were liquid doses, 103 were from products only available as tablets or capsules. Of the 257 electronically prescribed doses, 61 (24%) were not measurable. Of the 303 paper chart doses, 57 (19%) were not measurable. Of the 457 liquid doses 77 only needed up to 4% dose adjustment to become measurable. A further 10 doses required up to 9% dose adjustment. Drugs that were frequently prescribed as non-measurable doses were: diazepam, alimemazine, chloral hydrate, azithromycin, metronidazole, paracetamol & ibuprofen. Some doses were not measurable from tablets and no liquid is available in the Trust: clonidine, omeprazole, lansoprazole, nifedipine SR. 19/560 (3.4%) of medication orders required a dose to be measured to two decimal places: diazepam, morphine, clonazepam, furosemide, spironolactone, chloral hydrate, ranitidine, chlorothiazide, azithromycin, erythromycin. Conclusion: This audit has shown that by prescribing accurately as mg/kg without any dose rounding almost a quarter of doses cannot be measured accurately. Only a small dose adjustment is required to make the doses measurable. The current electronic prescribing system in use does not appear to have any automatic rounding, indeed the prevalence of difficult to measure doses was slightly worse (although not statistically significant, p value 0.19, Chi squared test), possibly because the prescriber doesn't "sense check" what they are prescribing as it is automated. Particular drugs with unusual strengths are often implicated in having harder to measure doses. Consideration should be made to round doses when prescribing and to add information regarding the strength of liquids available in local clinical guidelines.